Evaluation of the protection and release rate of bougainvillea (Bougainvillea spectabilis) extracts encapsulated in alginate beads. Issue 7 (3rd July 2019) - Orozco-Villafuerte, Juan; Escobar-Rojas, Alondra; Buendía-González, Leticia; García-Morales, Carla; Hernandez-Jaimes, Carmen; Alvarez-Ramirez, Jose
Abstract: There is a growing demand in the food industry for natural food products to replace synthetic ingredients. Motivated by this fact, the present work studied the extraction of coloring compounds from Bougainvillea spectabilis under aqueous and ethanolic conditions, and the encapsulation of the extract in alginate beads. Ethanolic extraction was more efficient as reflected by the higher values for total phenols (6.78 ± 0.24 mg EAG/g), betacyanins (5.04 ± 0.13 mg/g), betaxanthines (1.35 ± 0.06 mg/g, ) and inhibition capacity (81.31 ± 4.23%). FTIR analysis suggested the presence of interactions between the extract and the alginate chains. The release kinetics of compounds in alginate beads was measured under aqueous and ethanolic conditions at 25.0 °C and at 70.0 °C. Color was also monitored, showing that the color parameters followed a kinetics pattern similar to the released extract. However, the release of betalains exhibited a mixed behavior, reflecting interactions between the different compounds of the bougainvillea extract and the alginate chains. The extracts released from the beads were characterized to determine the preservation of their properties during encapsulation, concluding that the encapsulation is efficient to protect and release the bioactive compounds from bougainvillea extracts. Graphical Abstract: uf0001